One-stage resection of intravascular leiomyomatosis involving the right heart chamber through a single laparotomy - Wang, Chaonan; Shao, Jiang; Ma, Xiao; Zhou, Yan; Ma, Guotao; Cheng, Ninghai; Cao, Dongyan; Lai, Zhichao; Song, Xitao; Li, Kang; Liu, Bao (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This retrospective study aimed to summarize the feasibility and experience of utilizing a one-stage operation via single laparotomy to treat intracardiac leiomyomatosis (ICL). Materials and methods: A retrospective study of 13 patients with ICL who underwent one-stage resections was conducted at Peking Union Medical College Hospital from June 2015 to December 2021. All patients had their tumors removed by single laparotomy and were divided into a short venotomy group (6 cases) and an extensive venotomy group (7 cases). We reviewed the patient characteristics, surgical procedures, postoperative pathology, and perioperative and follow-up outcomes of all patients. Results: All patients underwent surgery for ICL resection using single laparotomy with a 100% success rate. Two patients had tumors distal to the right ventricle (RV), 2 patients had tumors that protruded into the RV in diastole and were confined to the right atrium (RA) in systole, and the other 9 patients had tumors confined to the RA that did not involve the tricuspid valve. The tumor was completely resected in 10 patients, yet 3 patients had a residual tumor. Six patients completed the surgery with short venotomy, 7 completed the surgery with extensive venotomy, and 9 underwent simultaneous total hysterectomy and bilateral adnexal resection. The mean operative time was 370.8 ± 111.0 minutes, and the mean blood loss was 992.3 ± 994.5 mL. Intraoperative blood loss was lower (483.3 ± 213.7 mL vs. 1429.2 ± 1208.0 mL; P=.020) and operative time was shorter (286.5 ± 71.9 minutes vs. 443.1 ± 84.4 minutes; P＝.004) in the short venotomy group than in the extensive venotomy group. At a mean follow-up of 26.3 ± 18.8 months, 1 patient had a local recurrence in the pelvis, and 1 patient died of pancreatic cancer, while the remaining patients had no recurrence during follow-up. Conclusions: One-stage resection of ICL patients by means of a single laparotomy is feasible and effective.